How they lived : the everyday lives of Hungarian Jews, 1867-1940 - Koerner, András (Central European University Press, 2015)
"This book consists of historical photographs and related text documenting the physical aspects of the lives of Hungarian Jews in the late 19th and early 20th centuries: the way they looked, the kind of neighborhoods and apartments they lived in, and the places where they worked"--Provided by publisher